Pengaruh dan Ancaman Globalisasi Terhadap Kebudayaan Indonesia - Husnul Hidayat (STAI DDI Kota Makassar, 2020)
Globalization is a process of international integration due to the exchange of worldviews, thoughts, cultural aspects and others. Simply, globalization can be interpreted as a worldwide process of things. So that the boundaries between countries are no longer a barrier and increasingly facilitated. There are many things that are affected because of globalization itself so that it can feel a positive or negative impact. It is natural when there is a change will definitely bring positive and negative impacts. Please note that globalization can never be avoided by a country. In everyday life, globalization also has an influence because of the exchange of values between cultures. Most will no longer stand alone but will pay attention to values globally.